Legal Protection for Female Workers from the Perspective of Employment Law - Hairul Anam; Yodha Mufarid Hidayat (Program Pascasarjana UIN Sumatera Utara Medan, 2025)
This study examines legal protection for female workers in Indonesia using descriptive qualitative methods through a literature review. The results indicate that protection is regulated in Law No. 13 of 2003, which provides special rights such as maternity leave, breastfeeding rights, and work hour regulations to prevent discrimination. However, in practice, obstacles remain, such as discrimination, weak oversight, and low legal awareness. Therefore, strengthened law enforcement, outreach, and affirmative action policies are needed to achieve fairness in the workplace